The influence of different microstructural constituents on the fatigue crack propagation behaviour of a nickel PM steel. (June 2017) - Mousavinasab, Saba; Blais, Carl
Highlights: Fatigue crack growth rates as a function of microstructural constituents. Retained austenite increases crack deviation without reducing crack growth rate. Strategies to improve fatigue of PM steels are identical to those for wrought steels. Abstract: Industrial applications of PM steels is increasing due to their intrinsic sustainability and low production costs. Nevertheless, fatigue properties of PM components are typically not as high as those of their wrought counterparts. Improving fatigue properties of PM steels relies on a deep understanding of the effect of their specific features such as porosity and matrix microstructure on the fatigue behaviour. The effect of porosity is already known, however, there exist lots of controversies on the effect of microstructural constituents and their propensity in lowering fatigue crack growth rates. In this study, a comprehensive approach was used to determine the effect of each microstructural constituent on fatigue crack propagation. A popular Ni admixed PM steel (FN0208) was chosen as study material since it is recognized to yield heterogeneous microstructures upon sintering. Moreover, two types of heat treatments were carried out to vary the volume fractions of microstructural constituents. Fatigue crack growth rates were measured for all heat-treated conditions using two R-ratios. A quantitative analysis was performed to characterize the spatial distribution of microstructural constituents on the fracture surfaces. Results show that, and contrary to what has been reported in literature, areas made of retained austenite or Ni-rich ferrite cause significant crack deflection, i.e. more tortuous crack path, but this behaviour does not translate into a reduction of the rate of fatigue crack propagation. Thus, the hardest phase, tempered martensite or bainite, are the ones that yield the lowest fatigue crack propagation rates albeit with a flatter, straighter crack path.